Performance Comparison Of The AFC-Crude Approximation And AFC-Fuzzy Logic Controllers In Reducing The Vibration Of The Suspended Handle - Jamaludin, Haziq (Universiti Sains Malaysia, 2017)
This study aims to suppress the vibration produced by any power tools to the suspended handle model using Active Force Control (AFC) method with embedded of an intelligent method. Prolonged use of the power tool with the high level of vibration can lead to the hand-arm vibration syndrome (HAVs). Due to this, a dynamic analysis of the suspended handle model is necessary in order to reduce the vibration of the system. The suspended handle is modelled as a single-degree-of-freedom (SDOF) system and a sine wave disturbance is applied to the system. Apart from that, some coefficients such as mass, spring and damper values and the control parameters are obtained from the previous study. In this simulation study, four systems are investigated and compared which are passive system, AVC with proportional-integration-derivative (PID), AVC with PID-AFC-Crude Approximation (CA) and AVC with PID-AFC-Fuzzy Logic (FL) controllers. From the previous study, the AFC scheme has been proven as a robust controller to the suspended handle. Based on this, the study is extended using the intelligent method (FL) to determine the AFC controller parameter which is an estimated mass (EM). From the study, the optimum EM obtained from CA method is 0.04 kg while for the FL method is 0.04223 kg. This value produced by the triangular-shaped membership function in the FL controller. In addition, overall performances are also compared by changing the target input value to zero and the AFCFL can still produce the best result to the system.